(untitled) (Sound Stage Screen, 2023)
This article analyzes the close relation between synthwave music and cinema, focusing on the role played by the former in paradigmatic films and TV series from the 1980s and the 2010s. To the two eras correspond two sets of semantic “associations,” which designate the functions and connotations embodied by synthwave in the cinematic context. The first analysis focuses on the context in which the association between the two protagonists of this affair has taken place for the first time, trying to understand why sci-fi cinema is often privileged when it comes to the association with (proto-)synthwave music—especially soundtracks by Tangerine Dream, John Carpenter, Giorgio Moroder and Vangelis, which are often referred to as main sources of inspiration for contemporary synthwave. The result is a first set of two “first-order associations” between synthwave and sci-fi cinema on the one side, and with the 1980s geek culture on the other. The focus then shifts towards the present times, exploring the ways in which synthwave soundtracks remediate 1980s popular culture by employing two “second-order associations” between synthwave and mediated, hyperreal versions of the 1980s and its products. In particular, the protagonists of this second analysis are the functions of synthwave soundtracks as an “age-synecdoche” and as an “aesthetic mediator,” especially in the series Stranger Things, in the movie It Follows, and in the late works by director Nicolas Winding Refn.